Metabolomic and microbiomic insights into color changes during the sweating process in Dipsacus asper - He, Hua; Xu, Jiao; Zhou, Taimin; Yang, Yang; Yang, Changgui; Xiao, Chenghong; Zhang, Chenggang; Li, Liangyuan; Zhou, Tao (Frontiers in Microbiology, 2023)
Sweating is one of the most important primary processing methods of Chinese medicinal materials. Dipsacus asper is a typical representative of sweating treatment that is recommended by the Chinese Pharmacopoeia. The color change of the fracture surface of the root is the prominent feature of sweating treatment. However, few studies have focused on the mechanism of color change during sweating treatment. In this study, widely targeted metabolomics and ITS high-throughput sequencing technologies were conducted to detect metabolites and microbial structure and diversity in the root of D. asper during sweating treatment. The results showed that a total of 668 metabolites including 36 down-regulated and 78 up-regulated metabolites were identified in D. asper following sweating treatment. The significantly differential metabolites were divided into 12 classes, including terpenoids and phenolic acids. Moreover, all the differential terpenoids were up-regulated and 20 phenolic acids showed a significant change after sweating treatment. In addition, the microbial community diversity and richness was increased following sweating treatment. The composition of microbial communities revealed that the relative abundance of Ascomycota and Basidiomycota weresignificantly changed after sweating treatment. Correlation analysis revealed that Ascomycota (Fusarium sp., Macrophomina sp., Ilyonectria sp., Metarhizium sp., Penicillium sp., Cyphellophora sp., Neocosmospora sp., unclassified_f_Nectriaceae and unclassified_o_Saccharomycetales) and Basidiomycota (Armillaria sp.) were associated with the content of terpenoids (6-DeoxyCatalpol and Laciniatoside Ⅲ) and phenolic acids (3-(4-Hydroxyphenyl)-propionic acid, Ethyl caffeate, 4-O-Glucosyl-4hydroxybenzoic acid, 2-Acetyl-3-hydroxyphenyl-1-O-glucoside, 4-O-Glucosyl-3,4dihydroxybenzyl alcohol, 3-O-Feruloylquinic acid, 3,4-O-Dicaffeoylquinic Acid Methyl Ester, O-Anisic acid, Coniferyl alcohol). We speculated that the Ascomycota and Basidiomycota affected the content of terpenoids and phenolic acids, resulting in the color change during sweating treatment in D. asper. This study provides a foundation for analyzing the mechanism in the processing of Chinese medicinal materials.